Teaching children with autism to mand for social information. Issue 4 (31st May 2020) - Landa, Robin K.; Frampton, Sarah E.; Shillingsburg, M. Alice
Abstract : We replicated Shillingsburg et al. (2018) by teaching children with autism to mand for social information while analyzing the variables influencing the emission of mands. We presented questions about a social partner that were known and observable (e.g., "What is Robin doing?"), known but unobservable (i.e., questions for which an intraverbal response had previously been taught, such as, "Where does Robin work?"), or unknown (e.g., "What is Robin's favorite food?"). Correct answers were reinforced across all conditions. During treatment, we prompted children to mand for information from the social partner following only unknown questions. All children acquired mands for social information and answered previously unknown questions correctly after manding for social information and 3 of 4 participants emitted mands to novel social partners, including a peer with autism.